Experimental tests of risky augmentation scenarios using Trinidadian guppies - Kronenberger, John Andrew, author; Angeloni, Lisa, advisor; Funk, Chris, advisor; Ghalambor, Cameron, committee member; Hufbauer, Ruth, committee member (Colorado State University. Libraries, 2017)
Increased isolation of populations, and the subsequent reduction in genetic diversity, can exacerbate global biodiversity loss by contributing to inbreeding depression and reducing the ability of organisms to adapt to rapid environmental change. This has prompted some conservation biologists to consider augmenting isolated populations with immigrants as a means of demographic and genetic rescue. Augmentations are typically highly successful, but they are also controversial due to the risk of outbreeding depression or the introduction of maladapted alleles when immigrants are genetically or adaptively divergent. For my Master's thesis, I tested risky augmentation scenarios using mesocosm populations of Trinidadian guppies (Poecilia reticulata) in two separate controlled experiments. In my first experiment (Chapter 1), I augmented mesocosm populations derived from a single recipient source with genetically or adaptively divergent immigrants to assess their short-term demographic effects. Mesocosms that were augmented maintained greater abundance and recruitment than controls that were not. There was also a trend for populations to receive a greater benefit from immigrants that were genetically divergent than those that were adaptively divergent. I expanded upon these results in my second experiment (Chapter 2), in which I augmented mesocosm populations from two different recipient sources with immigrants spanning a greater range of divergence and monitored them over a longer time frame, including an additional control and genetic monitoring to determine the relative impact of demography and genetics. Despite no evidence for demographic rescue, I found genetic rescue in one recipient population. Divergent immigrants did not have a negative effect in almost all cases, and any positive effect they had depended on the genetic diversity, immigrant fitness, and recipient life-history traits. Together, these experiments provide strong evidence that immigrants can bolster population fitness despite being divergent, thereby supporting the use of augmentation as a management technique in dire situations when no safe immigrant sources are available.